1998
DOI: 10.1159/000018616
|View full text |Cite
|
Sign up to set email alerts
|

Gastrin and the Enterochromaffin-Like Cell: An Acid Update

Abstract: Gastrin is synthesized and secreted mostly in a heptadecapeptide form from neurocrine G cells located in the antrum. The biologically active sequence of the molecule is a C-terminal pentapeptide, which has been conserved across many species. Transcriptional regulation of gastrin mRNA synthesis is positively regulated by transforming growth factor-α (TGF-α) and inhibited by somatostatin (SST). The inactive precursor form is converted to the active molecule by several posttranslation processing steps which inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
1
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 57 publications
1
26
1
1
Order By: Relevance
“…Histamine production is diminished by ϳ10% in the presence of the CCK2 blocker proglumide, suggesting that gastrin is active along this pathway. This finding is different than other studies, where in various species histamine is believed to be predominately mediated by gastrin to elevate acid secretion (11,15,19,20). Although we show that this pathway is active in the guinea pig, no other studies have monitored both the direct and indirect gastrin pathways leading to the activation of the parietal cell in one experiment on any species.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Histamine production is diminished by ϳ10% in the presence of the CCK2 blocker proglumide, suggesting that gastrin is active along this pathway. This finding is different than other studies, where in various species histamine is believed to be predominately mediated by gastrin to elevate acid secretion (11,15,19,20). Although we show that this pathway is active in the guinea pig, no other studies have monitored both the direct and indirect gastrin pathways leading to the activation of the parietal cell in one experiment on any species.…”
Section: Discussioncontrasting
confidence: 99%
“…Although we show that this pathway is active in the guinea pig, no other studies have monitored both the direct and indirect gastrin pathways leading to the activation of the parietal cell in one experiment on any species. However, other studies have shown that when acid secretion is monitored, inhibitors of the gastrin pathway diminish acid secretion (16,20) or when histamine is monitored, gastrin elevates levels of histamine (15,19,23,29). Our data are supportive of both these studies, but provide further information in the degree gastrin plays in both pathways.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This negative result may reflect the fact that the gastrin gene product is extensively posttranslationally modified in G cells (21,44,48) to produce the various different forms of gastrin. The preprogastrin protein is converted to multiple different forms of gastrin, including progastrin, glycine-extended gastrin and amidated gastrins.…”
Section: Discussionmentioning
confidence: 99%
“…The microarray analysis indicated that cells infected with AdBMRF1 expressed the cellular gastrin gene at a 34-fold-higher level than the mock-infected cells or the AdLacZ-infected cells (data not shown). Since gastrin expression is normally limited to specialized neuroendocrine-like cells in the stomach (the G cells) (21), the finding that BMRF1 (Fig. 1a).…”
Section: Bmrf1 Activates Gastrin Expressionmentioning
confidence: 99%